La fin de la domination (masculine) Pouvoir des genres, féminismes et post-féminisme queer - Bourcier, Sam (M.H) (Multitudes, 2003)
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; europe; fem1000; france; genre; identités LGBTQIA2+; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques

Catching a wave: reclaiming feminism for the 21st century - Dicker, Rory Cooke; Piepmeier, Alison (Northeastern University Press, 2003)
Young women today have benefited from the strides made by grassroots social activists in the 1960s and 1970s, yet they are hesitant to identify themselves as feminists and seem apathetic about carrying the torch of older generations to redress persistent sexism and gender-based barriers. Contesting the notion that we are in a post-feminist age, this collection of essays identifies a third wave of feminism. The contributors argue that the next generation needs to develop a politicized, collective feminism that both builds on the strategies of second wave feminists and is grounded in the material realities and culture of the 21st century. Organized into five sections which mirror the stages of consciousness-raising, the book looks at a broad range of perspectives on the diversity, complexity, multiplicity and playfulness of the third wave. It is also a call to action for new voices to redefine a feminism that is not only personally aware, but also politically involved. (source: Nielsen Book Data)
Section: x, 338 p. ; 24 cm Table des matières Introduction / Rory Dicker and Alison Piepmeier The "big lie": false feminist death syndrome, profit, and the media / Jennifer L. Pozner In a word, Baywatch / Susannah B. Mintz. Reviving Lolita ; or, because junior high is still hell / Alyssa Harad "That's not fair!" : nurturing girls' natural feminism / Nancy Gruver Voices and visions : a mother and daughter discuss coming to feminism and being feminist / Roxanne Harde and Erin Harde Please–stop thinking about tomorrow : building a feminist movement on college campuses for today / Sarah Boonin Who's the next Gloria? : the quest for the third wave superleader / Jennifer Baumgardner and Amy Richards Buffy the vampire slayer : the next generation of television / Michele Byers Third World, third wave feminism(s) : the evolution of Arab American feminism / Susan Muaddi Darraj Feminism's family problem : feminist generations and the mother-daughter trope / Astrid Henry Do the ladies run this– ? Some thoughts on hip-hop feminism / Gwendolyn D. Pough The transfeminist manifesto / Emi Koyama Hearing the daughter voice : The Bat Kol as Rrrabbi Grrrl / Alana Suskin Rocking the gender order / Mimi Schippers Pranks and fake porn : doing feminism my way / Kristina Sheryl Wong Afterword / Katha Pollitt and Jennifer Baumgardner.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; féminisme pop; militance; premier cycle; périodes historiques; soc2014; thématiques; transféminisme; troisième vague

Dictionnaire des cultures gays et lesbiennes - Eribon, Didier; Haboury, Frédéric; Lerch, Arnaud (Larousse, 2003)
Dictionnaire illustré et international consacré aux cultures gays et lesbiennes contemporaines (depuis la fin du XIXe siècle). Plus de 570 articles(2 millions de signes en tout), dont 50 dossiers thématiques, qui couvrent tous les aspects du sujet : - références culturelles et artistiques communes (d'Absolutely Fabulous à Virginia Woolf, de Pedro Almodóvar à Andy Warhol.), - associations (Act Up.), - théoriciens (Michel Foucault.), - événements (Lesbian and Gay Pride.), - mours et modes de vie (sida, sexualités.), - aspects légaux (couple, adoption.), - gay and lesbian studies (histoire, sociologie, queer theory.), etc.
Section: 548 pages : illustrations (certaines en couleur), photogr. (certaines en couleur) ; 27 cm
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; histoire et politique; militance; outils; ouvrages de références; premier cycle; périodes historiques; queer; sexualité; soc2014; thématiques; études gaies et lesbiennes

L'union civile: nouveaux modèles de conjugalité et de parentalité au 21e siècle : actes du colloque du Groupe de réflexion en droit privé - Lafond, Pierre-Claude; Lefebvre, Brigitte; Université du Québec à Montréal Groupe de réflexion en droit privé. (Éditions Y. Blais, 2003)
Textes présentés lors d'un colloque organisé par le Groupe de réflexion en droit privé et tenu à la Faculté de science politique et de droit de l'Université du Québec à Montréal, le 10 octobre 2002.
Section: xiv, 399 pages : illustrations ; 23 cm
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits; histoire et politique; identités LGBTQIA2+; militance; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Intersexe et transsexualités : Les technologies de la médecine et la séparation du sexe biologique du sexe social - Löwy, Ilana (Cahiers du Genre, 2003)
Le sexe social est construit sur un mode binaire. Par contre, le sexe biologique se présente comme un continuum, avec, aux deux extrêmes, les « sexes biologiques » clairement définis et, au milieu, une large gamme de situations intermédiaires — des individus « intersexe ». De tels individus remettent en cause nos certitudes sur la stabilité des catégories « homme » et « femme ». Cet article trace l’histoire des interventions médicales ayant pour but de corriger l’anomalie de l’intersexe et de produire des êtres humains dont le corps ne remet pas en cause la bipolarité du féminin et du masculin. Il suit les débats sur les liens supposés entre intersexualité et homosexualité puis expose la transition du traitement de l’intersexualité à celui de la transsexualité. Il étudie enfin le rôle des nouvelles techniques de la médecine dans la séparation entre le « sexe » et le « genre ». La possibilité de moduler les paramètres du « sexe biologique » permet alors une réflexion sur le « sexe social » comme variable indépendante des structures biologiques.
Number: 1 Publisher: L'Harmattan
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme

Queer theory and communication: from disciplining queers to queering the discipline(s) - Yep, Gust A.; Lovaas, Karen; Elia, John P. (Harrington Park Press, 2003)
Get a queer perspective on communication theory! Queer Theory and Communication: From Disciplining Queers to Queering the discipline(s) is a conversation starter, sparking smart talk about sexuality in the communication discipline and beyond. Edited by members of "The San Francisco Radical Trio," the book integrates current queer theory, research, and interventions to create a critical lens with which to view the damaging effects of heteronormativity on personal, social, and cultural levels, and to see the possibilities for change through social and cultural transformation. Queer Theory and Communication represents a commitment to positive social change by imagining different social realities and sharing ideas, passions, and lived experience. As the communication discipline begins to recognize queer theory as a vital and viable intellectual movement equal to that of Gay and Lesbian studies, the opportunity is here to take current queer scholarship beyond conference papers and presentations. Queer Theory and Communication has five objectives: 1) to integrate and disseminate current queer scholarship to a larger audience-academic and nonacademic; 2) to examine the potential implications of queer theory in human communication theory and research in a variety of contexts; 3) to stimulate dialogue among queer scholars; 4) to set a preliminary research agenda; and 5) to explore the implications of the scholarship in cultural politics and personal empowerment and transformation.
Section: xxx, 415 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; communication; cours; disicpline; premier cycle; périodes historiques; queer; régions géographiques; soc2014; systèmes d'oppressions; thématiques; états-unis